(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
The culture of the Italian immigrant experience worldwide has been characterized by daily dynamics of adaptations and transformations deeply shaping the processes of identity-formation. By looking at the diverse and decade-long linguistic metamorphoses we can start to reclaim the importance of a literary production too often overlooked (both in its âinstitutionalâ works and in its more personal autobiographical expressions) â and at the same time re-evaluate the complex creativity of its linguistic fabric. KEYWORDS: Italians in the U.S., Italian migration, Language and literature, Italian language abroad, Italian American poetry and fiction